2007
DOI: 10.1017/s1368980007382487
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns and survival of older Europeans: The EPIC-Elderly Study (European Prospective Investigation into Cancer and Nutrition)

Abstract: Objective: To investigate the association of a posteriori dietary patterns with overall survival of older Europeans. Design and setting: This is a multi-centre cohort study. Cox regression analysis was used to investigate the association of the prevailing, a posteriori-derived, plant-based dietary pattern with all-cause mortality in a population of subjects who were 60 years

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(92 citation statements)
references
References 55 publications
5
83
1
3
Order By: Relevance
“…The prudent pattern detected by PCR was associated with lower all-cause mortality, whereas the PCR-derived western pattern yielded discrepant results (Osler et al, 2001;Heidemann et al, 2008). Bamia et al (2007) found that a plant-based diet is not associated with mortality in Germany, but in several other countries such as Greece and Denmark. This study has several strengths.…”
Section: Discussionmentioning
confidence: 95%
“…The prudent pattern detected by PCR was associated with lower all-cause mortality, whereas the PCR-derived western pattern yielded discrepant results (Osler et al, 2001;Heidemann et al, 2008). Bamia et al (2007) found that a plant-based diet is not associated with mortality in Germany, but in several other countries such as Greece and Denmark. This study has several strengths.…”
Section: Discussionmentioning
confidence: 95%
“…Results from the European Prospective Investigation into Cancer and Nutrition suggested that the relationship between a plant-based diet and mortality in those aged 60+ years may be country-specific since there were relatively strong associations in Greece, Spain, Denmark and the Netherlands, but no associations in the UK and Germany (29) . The consequences of dietary patterns rich in dairy products for mortality seem to be inconsistent.…”
Section: Mortality and Life Expectancymentioning
confidence: 99%
“…The Epidemiological Prospective Study in Cancer (EPIC) has reported dietary patterns in adults and elderly individuals in 10 European countries (Bamia et al, 2007;Masala et al, 2007;Touvier et al, 2009) using locally designed FFQs. Comparisons of dietary patterns were usually studied with a single 24-h recall questionnaire, standardised for all participant countries.…”
Section: Introductionmentioning
confidence: 99%